2017
DOI: 10.5424/sjar/2017153-10901
|View full text |Cite
|
Sign up to set email alerts
|

A bio-economic model to improve profitability in a large national beef cattle population

Abstract: A bio-economic model was developed for estimating economic values for use in improving profitability in a large national beef cattle population from birth to slaughter. Results were divided into fattening costs, production costs and income. Economic values were derived for 17 traits for two regions, mature weight (-0.43 € and -0.38 €/+1 kg of live weight), age at first calving (-0.13 € and -0.11 €/+1d), calving interval (-1.06 € and -1.02 €/+1d), age at last calving (0.03 € and 0.03 €/+1d), mortality 0-48 h (-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Economic weights in the selection indices for each scenario were derived from a bioeconomic model based on López‐Paredes, Jiménez‐Montero, Pérez‐Cabal, González‐Recio, and Alenda (). The three scenarios were:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Economic weights in the selection indices for each scenario were derived from a bioeconomic model based on López‐Paredes, Jiménez‐Montero, Pérez‐Cabal, González‐Recio, and Alenda (). The three scenarios were:…”
Section: Methodsmentioning
confidence: 99%
“…A profit function was developed expressing benefits in €/slaughtered calf/year (López‐Paredes et al., ) calculated as incomes minus costs as follows: Profit=false(IFATPRODfalse)×cnormalsEMnormalCwhere I is the income per slaughtered calf at fixed age at slaughter, FAT is the fattening cost of calves in feedlot to meet energy requirements at fixed age at slaughter, PROD is the production cost per slaughtered calf, including feeding cost of heifers, cows and culled cows to meet their energy requirements minus income per culled cow carcass at sale, c s is 365/AS, EM C is expressed in €/per slaughtered calf/year calculated as the cost of M calf and M cow with a carbon tax value ( t ) per kg of CH 4 as: EMnormalc=t×false(Mcalf+Mcowfalse)…”
Section: Methodsmentioning
confidence: 99%
“…The estimated heritability of 0.17 and its economic importance (López-Paredes et al, 2017) indicated that AFC should be included in a maternal/replacement index to select for improved profit. This heritability is similar to that shown by Caetano et al (2013), Boligon et al (2010), and Boligon and Albuquerque (2011) in Nellore cattle and less than the 0.23 reported by Goyache and Gutierrez (2001), the 0.28 reported by Minick-Bormann (2010), and the 0.31 reported by Berry and Evans (2014).…”
Section: Discussionmentioning
confidence: 99%
“…Gutiérrez et al (2002) reported a positive correlation of 0.23 between CI and AFC, which is similar to the 0.14 found in this study. The economic value of AFC is −$0.192/d (−0.16€/d) per young animal slaughtered (López-Paredes et al, 2017). This amounts to −$5.676 (−4.73€) per young animal slaughtered per unit of additional variance of AFC (27 d) and phenotypic deviation (163 d; Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation